Comparing Efficacy of Analgesic Modalities in Patients Undergoing Total Knee Arthroplasty [Letter] - Gao Y; Xue FS; Li CW (Dove Medical Press, 2022)
Ying Gao, Fu-Shan Xue, Cheng-Wen Li Department of Anesthesiology, Beijing Friendship Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Fu-Shan Xue, Department of Anesthesiology, Beijing Friendship Hospital, Capital Medical University, 95 Yong-An Road, Xi-Cheng District, Beijing 100050, People’s Republic of China, Tel +86-139-1117-7655, Fax +86-10-63138362, Email xuefushan@aliyun.com; fushanxue@outlook.com View the original paper by Ms Xiao and colleagues